A Study on Consumer Behaviour of Passenger Car Segments through Logistic egression Modelling. Issue 1 (June 2017) - Menon, Balakrishnan
The automobile industry in India was highly protected in favour of domestic car manufacturers till the late 1980s. The Government of India's drastic shift towards economic liberalization and Foreign Direct Investment Policy transformed the automobile industry, since the early 1990s. The ensuing decade witnessed many foreign car manufacturers entering the Indian automobile industry with their models and brands. World leaders in passenger cars such as Toyota, Honda, General Motors, Ford, and Hyundai set up manufacturing hubs in India, cashing on the liberalized Foreign Direct Investment Policy of the Government of India. These manufacturers captured the hearts and minds of Indian car customers, with their choicest of car models with high technological and innovative product offerings, with quality and reliability. This transformed the automobile scene from a seller's market to buyer's market. Car customers had started developing their own personal preferences and purchasing patterns, which were hitherto unknown in the Indian automobile segment. This study focused on the influences of various attributes and factors in the consumer purchase behaviour of passenger cars. The logistic modelling approach evaluated as to why the car customers prefer different car segmented models in comparison to a base category model. The article attempted to build a passenger car purchase modelling approach, to evaluate consumer behavioural preferences, which eventually influences the purchase behaviour of passenger car owners. The results of the research would contribute to the practical knowledge base of the automobile industry, specifically to the passenger car segments. The model developed has also a great contributory value addition, to the manufacturers and dealers, for evolving a customized marketing strategy approach.